2008
DOI: 10.1007/s12020-008-9067-9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the synthetic liver X receptor agonist T0901317 on the growth hormone and thyroid hormone axes in male rats

Abstract: Liver X receptors (LXRs), activated by oxysterols, play an important role in the regulation of lipid and glucose metabolism, which is also markedly dependent on thyroid hormone and growth hormone (GH) status. Here, we investigated how a 1-week exposure to the synthetic LXR agonist T0901317 affected GH secretion and thyroid hormone status in male rats. While the pulse frequency of GH secretion was marginally affected there was a highly significant decrease in the triiodo-L-thyronine/thyroxine (T3/T4) ratio in p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 56 publications
0
3
1
Order By: Relevance
“…Our observation that stimulation of LXRα by TO increased the expression of hDIO1 in HepG2 cells was inconsistent with previous in vivo observations that TO decreases hepatic expression of Dio1 in rat and mouse models [37,38]. Importantly, there is a large difference in the sequences of this gene’s promoter regions between human and rodent; TREs have not been identified in the promoter regions of rat or mouse Dio1 , whereas two TREs are present in the promoter region of human DIO1 [3].…”
Section: Discussioncontrasting
confidence: 99%
“…Our observation that stimulation of LXRα by TO increased the expression of hDIO1 in HepG2 cells was inconsistent with previous in vivo observations that TO decreases hepatic expression of Dio1 in rat and mouse models [37,38]. Importantly, there is a large difference in the sequences of this gene’s promoter regions between human and rodent; TREs have not been identified in the promoter regions of rat or mouse Dio1 , whereas two TREs are present in the promoter region of human DIO1 [3].…”
Section: Discussioncontrasting
confidence: 99%
“…This intervention may be especially effective by promoting both efficient cholesterol recycling and removal of inflammation-promoting myelin debris (Lefterov et al, 2007; Zelcer et al, 2007) that may help combat age-related reduction of successful remyelination (Shen et al, 2008; Shields et al, 1999). Such interventions may have serious systemic side effects however (Cheng et al, 2008a; Davies et al, 2008). …”
Section: Future Directions and Treatment Implicationsmentioning
confidence: 99%
“…In addition, others have shown that LDLr Ϫ / Ϫ mice transplanted with LXR ␣ ␤ Ϫ / Ϫ bone marrow demonstrate a 3-fold increase in atherosclerosis in the absence of changes in plasma lipids. (154) Unfortunately, systemic administration of fi rst generation LXR agonists results in elevated plasma triglycerides, fatty liver (155,156) , and disturbance of growth hormone and thyroid axes (157). These studies show that cholesterol mobilization from the vascular macrophage constitutes an important step in atheroprotection.…”
Section: Lxrmentioning
confidence: 99%